2020
DOI: 10.3389/fsurg.2019.00074
|View full text |Cite
|
Sign up to set email alerts
|

The BMI Paradox and Robotic Assisted Partial Nephrectomy

Abstract: Introduction: Partial nephrectomy (PN), has become the gold standard for the surgical management of small renal masses, due to excellent oncologic control with concomitant preservation of nephron units. However, data regarding the association of obesity with perioperative outcomes following PN are mixed. Therefore, the association between obesity (using BMI) and post-operative complications (POC) rate following Robotic assisted laparoscopic PN (RPNx) was tested. Methods: Two hundred and fifty-one adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Other studies found no relationship between obesity and any complications ( 19 - 21 ) or major complications ( 22 ). Kott et al found in 251 patients treated with robot-assisted partial nephrectomy that increasing BMI decreased complications rates up till an inflection point of 30 kg/m 2 , while above that point higher BMI was associated with higher complication rates ( 23 ). The precise relationship remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found no relationship between obesity and any complications ( 19 - 21 ) or major complications ( 22 ). Kott et al found in 251 patients treated with robot-assisted partial nephrectomy that increasing BMI decreased complications rates up till an inflection point of 30 kg/m 2 , while above that point higher BMI was associated with higher complication rates ( 23 ). The precise relationship remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Wiens [15] showed that obese patients undergoing LPN are not at significantly increased risk of complication relative to non-obese patients and that comorbidity status and R.E.N.A.L.-score should be the main criteria to take into account to evaluate feasibility for LPN. On the contrary, Kott [16] found that a BMI over 30 kg/m 2 was a significant factor for POC associated with robot assisted LPN. In our analysis there was a relative significant correlation between achievement of intraoperative Trifecta and BMI.…”
Section: Ebl Is the First Component In Our Definition And Intraoperative Hemorrhagementioning
confidence: 93%
“…In this cohort study of 117 patients, the female/male ratio was 1.54 (71/46), the mean age was 60.4 years (range 17-89 years) and the mean body mass index (BMI) was 25.5 (range [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. As detailed in Table 1, patients were mostly ASA (American Society of Anaesthesiologists classification) II at the time of operation.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Interestingly, a BMI higher than 23 was associated to lower rate of post-operative complications, raising questions on the potential protective role of intra-abdominal fat around the hiatus that may reduce local inflammatory response 25 .…”
mentioning
confidence: 99%